Enacting competition, capacity, and collaboration: performing neoliberalism in the U.S. in the era of evidence-based interventions. Issue 3 (27th May 2022) - Snell-Rood, Claire; Trott Jaramillo, Elise; Gunderson, Lara; Hagadone, Sarah; Fettes, Danielle; A. Aarons, Gregory; Willging, Cathleen
ABSTRACT: Funders increasingly encourage social and health service organizations to strengthen their impact on public health through the implementation of evidence-based interventions (EBIs). Local governments in the U.S. often utilize market-based contracting to facilitate EBI delivery via formal relationships with non-governmental community-based organizations (CBOs). We sought to understand how the discourses embedded within contracting to compete and perform influence how CBOs represent and accomplish their work. We draw on qualitative interviews conducted with government administrators (N = 16) overseeing contracts for one child welfare EBI, SafeCare® and the leaders (N = 25) of organizations contracted to implement this program. Participants endorsed competition, capacity, and collaboration as ideals within marketized contracting. Yet they expressed doubt about marketplace meritocracy and described the costs incurred in building the necessary organizational infrastructure to deliver EBIs and compete for contracts. We discuss the implications of marketized EBI contracting for CBOs and the limitations it poses for evidence-based public health, especially in socially marginalized communities.